The study of attitudes, prejudices and stereotypes towards the blind and people of visually impaired - Oláh, Judit (Acta Agraria Debreceniensis, 2013)
Living with visual impairment is not only a state but it is also a social connection. This relationship has two directions: on one hand it means belonging to the community of the blind and visually impaired, and on the other hand it means the lack of belonging to the healthy population. To study their situation and to tackle the issue of their social and work-related integration is an essential goal for this particular disadvantaged group as well as for the society. In my research I have examined how intensive and of what scale the emloyers’ attitude, stereotypes and prejudices towards the blind and visually impaired are. The research was centred around the measure of attitude, which was carried out with the help of an Osgood semnatic difference scale.